The Influence of Principal Leadership and Work Ethic of Civil Servant Teachers on Teacher Performance - Amiati, Amiati; Kristiawan, Muhammad; Wardiah, Dessy (Journal of Social Work and Science Education, 2021)
The function of principal leadership in the successful delivery of education in schools is critical. It is possible to optimize the work ethic of teachers in their tasks via strong leadership. It is considered that if leadership is carried out successfully and work ethic is ideal, it would be able to support instructors' good performance. As a result, the purpose of this study was to determine the impact of a principal's leadership and a teacher's work ethic on teacher performance. This study was carried out using quantitative research methodologies. According to the findings of this study, the principal's leadership and teacher work ethic had a favorable and substantial impact on the performance of state junior high school teachers, both partially and concurrently.